2015
DOI: 10.1186/s13256-015-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute neck pain caused by septic arthritis of the lateral atlantoaxial joint with subluxation: a case report

Abstract: IntroductionCrystal-induced arthritis of the lateral atlantoaxial joint may be intimately involved in acute neck pain in the elderly. Patients typically have a good prognosis, and symptoms usually subside within a few weeks. On the other hand, septic arthritis of the lateral atlantoaxial joint requires early diagnosis and antibiotic treatment. Diagnostic delay is a risk factor for an unfavorable outcome of vertebral osteomyelitis. Even though septic arthritis of the lateral atlantoaxial joint is a very rare cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…However, this case illustrates how potentially fatal this diagnosis is, with the patient experiencing severe sepsis and requiring respiratory and renal support. Previous cases of cervical septic arthritis report a more insidious course, with symptoms of neck pain progressing over months before requiring intervention 4. In contrast, in this case the patient only experienced symptoms for 2 days, with rapid progression to septic shock and multiorgan failure.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, this case illustrates how potentially fatal this diagnosis is, with the patient experiencing severe sepsis and requiring respiratory and renal support. Previous cases of cervical septic arthritis report a more insidious course, with symptoms of neck pain progressing over months before requiring intervention 4. In contrast, in this case the patient only experienced symptoms for 2 days, with rapid progression to septic shock and multiorgan failure.…”
Section: Discussionmentioning
confidence: 53%
“…Cervical facet joint arthritis is even rarer, with only a small number of reported cases worldwide. There are 10 previous cases of septic arthritis affecting the cervical spine, involving the atlanto-axial facet joints (five cases)4 and the subaxial cervical facet joints (five cases) 5–8. Here, we present a near fatal case of subaxial cervical facet joint septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…A common site of septic arthritis of the facet joint is the lumbar spine, which is reported in approximately 90% cases . Only a few cases of cervical facet infection similar to this case have been reported . In those cases, unilateral neck pain was the initial presentation, with rapid symptom progression.…”
mentioning
confidence: 66%
“…Calcium pyrophosphate dihydrate crystal deposition disease or pseudogout is characterised by deposition of CPPD crystals in hyaline cartilage and fibrocartilage. Like septic arthritis, pseudogout of the cervical vertebral joints would present with acute posterior neck pain, fever and neck stiffness, making differentiating the two fairly difficult without joint aspiration 10. One retrospective study from 2013 identified the prevalence of crystal disease in joint fluid of patients with previously diagnosed arthritis of those joints.…”
Section: Discussionmentioning
confidence: 99%